2008
DOI: 10.1002/jobm.200700365
|View full text |Cite
|
Sign up to set email alerts
|

Stress adaptations in a Plant Growth Promoting Rhizobacterium (PGPR) with increasing salinity in the coastal agricultural soils

Abstract: The costs associated with soil salinity are potentially enormous and the effects of salinity may impact heavily on agriculture, biodiversity and the environment. As the saline areas under agriculture are increasing every year across the globe, it is of much public concern. Agricultural crops and soil microorganisms are affected with salinity. As Plant Growth Promoting Rhizobacteria (PGPR) have been reported to be contributing to the plant health, the osmotolerance mechanisms of these PGPRs are of importance. P… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
64
0
2

Year Published

2011
2011
2023
2023

Publication Types

Select...
4
4
1

Relationship

1
8

Authors

Journals

citations
Cited by 195 publications
(73 citation statements)
references
References 21 publications
1
64
0
2
Order By: Relevance
“…Our bacterial strains are salt tolerant up to 3% NaCl and temperature resistant (Egamberdieva and Kucharova 2009), thus they were able to survive in the rhizosphere of bean due to their competitiveness and persistence in saline arid soil conditions. Similar results were obtained by Paul and Nair (2008) whereas the root colonization potential of the salt tolerant Pseudomonas strain was not hampered with higher salinity in soil. Diby et al (2005) also observed that the population of the P. pseudoalcaligenes MSP-538 did not change considerably with increasing salinity in the soil.…”
Section: Resultssupporting
confidence: 85%
See 1 more Smart Citation
“…Our bacterial strains are salt tolerant up to 3% NaCl and temperature resistant (Egamberdieva and Kucharova 2009), thus they were able to survive in the rhizosphere of bean due to their competitiveness and persistence in saline arid soil conditions. Similar results were obtained by Paul and Nair (2008) whereas the root colonization potential of the salt tolerant Pseudomonas strain was not hampered with higher salinity in soil. Diby et al (2005) also observed that the population of the P. pseudoalcaligenes MSP-538 did not change considerably with increasing salinity in the soil.…”
Section: Resultssupporting
confidence: 85%
“…It is also suggested that root-colonising bacteria which produce phytohormones, when bound to the seed coat of a developing seedling, may act as a mechanism for plant growth stimulation and these organisms can prevent the deleterious effects of stresses from the environment (Lindberg et al 1985, Frankenberger andArshad 1995). The beneficial attributes of these organisms also include improved nutrient recycling in the rhizosphere microcosm and root colonization are some of the challenges under stress (Mayak et al 2004, Paul and Nair 2008, Berg 2009, Lugtenberg and Kamilova 2009. P. extremorientalis TSAU20 and P. chlororaphis TSAU13 showed their capacity to increase the growth of various crops under saline conditions Kucharova 2009, Egamberdieva et al 2010).…”
mentioning
confidence: 99%
“…This increase in soil moisture and organic content can support the survival and growth of plant-growth promoting rhizobacteria (PGPR). Thus, cyanobacterial growth positively alters the chemical and physical property of soils, and PGPRs along with EPSproducing cyanobacteria may contribute to an improvement and reclamation of infertile soils (Flaibani et al, 1989;Verrecchia et al, 1995;Zulpa et al, 2003;Paul and Nair, 2008). The consortium of PGPR and cyanobacteria increases the plant growth by improving the soil fertility and nutrient utilization.…”
Section: Cyanobacteria and Sustainable Agriculturementioning
confidence: 99%
“…More also, it reduces ion activity in soil solution thereby, leading to nutrient deficiency and reduction of overall growth and yield quality of plant. Paul and Nair (2008), stress that plants become vulnerable to soil borne diseases under saline stress In the past, some of the strategies employed to alleviate salt stress include the following: leaching of excess soluble salts from upper to lower soil depth, developing salt resistant cultivars, harvesting salt accumulating aerial plant parts in areas with negligible irrigation (Karthikeyan et al 2012). These strategies are labour intensive and highly scientific.…”
Section: Benefits Of Microbial Inoculation In Saline Soilmentioning
confidence: 99%